Faktor-Faktor yang Memengaruhi Nilai Perusahaan dengan Akuntansi Lingkungan sebagai Variabel Moderasi - Dian Permata; Khomsiyah Khomsiyah (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze the effect of environmental accounting as a moderating variable on the relationship with factors that affect firm value consisting of firm size, profitability, board of commissioners size, and firm age. The population of this study is the Consumer Cyclicals sector companies in hotels that are officially listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. By using purposive sampling, the sample of this research are 54 companies. The criteria for the sample companies used are companies that are Consumer Cyclicals sector companies in hotels that are officially listed on the IDX on an ongoing basis during the period 2019 to 2021, companies that publish an annual report on the IDX for a specified period, and its financial statements are reported using the rupiah currency. This research method uses a quantitative approach with data analysis using Moderated Regression Analysis (MRA). The  results  of  the  study  simultaneously  firm size, profitability, board of commissioners size, and firm age  affect  the  firm value  of  the  Consumer Cyclicals sector companies in hotels on  the  Indonesia  Stock  Exchange  in  the  2019- 2021  period  of  16.3%  the  remaining  influenced  by  other variable. Based on the conclusions generated from the factors used that affect firm value, only firm size has an significant effect on firm value, while other factors such as profitability, board of commissioners size, and firm age have no significant effect on firm value.